IMPLEMENTASI KEBIJAKAN PENGEMBANGAN UED-SP MENJADI BUMDES DI KABUPATEN ROKAN HULU (STUDI KASUS BUMDES MEKAR SARI DESA RAMBAH BARU KECAMATAN RAMBAH SAMO) - Delia, Galih; Rusli SD, Zaili (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Based on economic development in the village has long been run by the government. Village-owned enterprises (BUMDes) is an economic institutions at the village level aims to manage the potential welfare villages and rural communities that are managed by the village government and the community. The establishment of the village-Owned Enterprises carried out by aspiration of the people and the government village through village consultation. The purpose of this research is to know the Implementation Of Development Policy Of UED-SP Into BUMDes In Rokan Hulu District (Case Study BUMDes Mekar Sari Rambah Baru Village Rambah Samo Subdistrict). Theoretical concepts used by the researchers are the factors that influence the implementation of policies used by George Edward III where the indicators used are communication, resources, disposition and bureaucratic structure. This research uses qualitative descriptive method, using interview technique, observation and documentation. The result of this research shows that the implementation of development policy of UED-SP into BUMDes in Rokan Hulu District has not been run in accordance with the purpose of forming BUMDes and not yet able to help improve the village economy. There are still some obstacles in the implementation of policies and management of BUMDes such as the limited human resources to be a companion team to oversee BUMDes in every village, the type of business that is run is still limited and coordination between the BUMDes and the village government is less than be maximum because the village head is less supportive with the BUMDes program. Keywords: Policy Implementation, Development, Village-Owned Enterprises (BUMDes)